Determinación de síntomas depresivos en estudiantes adolescentes de una Institución Educativa (2023)
Depression in adolescents is a public health problem that has been increasing in recent years; therefore, the objective of this research is to describe the depressive symptomatology in adolescent students of an institution located in the rural area of the municipality of Ortega - Tolima.